Barley-based probiotic food mixture: health effects and future prospects. Issue 29 (17th October 2022) - Sharma, Ruchi; Mokhtari, Samira; Jafari, Seid Mahdi; Sharma, Somesh
Abstract: Consumers around the globe are increasingly aware of the relation between nutrition and health. In this sense, food products that can improve gastrointestinal health such as probiotics, prebiotics and synbiotics are the most important segment within functional foods. Cereals are the potential substrates for probiotic products as they contain nutrients easily assimilated by probiotics and serve as the transporters of Lactobacilli through the severe conditions of gastrointestinal tract. Barley is one of the important substrates for the probiotic formulation because of its high phenolic compounds, β-glucans and tocols. The purpose of this review is to examine recent information regarding barley-based probiotic foods with a specific focus on the potential benefits of barley as a substrate for probiotic microorganisms in the development of dairy and nondairy based food products, and to study the effects of food matrices containing barley β-glucans on the growth and features of Lactobacillus strains after fermentation.